2016
DOI: 10.3390/ijms17122001
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ERK1/2 in the Development of Diabetic Cardiomyopathy

Abstract: Diabetes mellitus is a chronic metabolic condition that affects carbohydrate, lipid and protein metabolism and may impair numerous organs and functions of the organism. Cardiac dysfunction afflicts many patients who experience the oxidative stress of the heart. Diabetic cardiomyopathy (DCM) is one of the major complications that accounts for more than half of diabetes-related morbidity and mortality cases. Chronic hyperglycemia and hyperlipidemia from diabetes mellitus cause cardiac oxidative stress, endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 106 publications
2
65
0
Order By: Relevance
“…RAS proteins signal through multiple effector pathways, including the MEK/ERK (MAPK) and PI3K/AKT pathways, which have been investigated extensively and are related to various cardiac diseases [24, 25]. This study showed that RASA1 was responsible for the effects of miR-223 in CFs.…”
Section: Resultsmentioning
confidence: 77%
“…RAS proteins signal through multiple effector pathways, including the MEK/ERK (MAPK) and PI3K/AKT pathways, which have been investigated extensively and are related to various cardiac diseases [24, 25]. This study showed that RASA1 was responsible for the effects of miR-223 in CFs.…”
Section: Resultsmentioning
confidence: 77%
“…29 The ERK-MAPK signalling pathway is closely associated with multiple damages in diabetes, and at the same time, NF-kB is in the most critical position in the entire MAPK signalling pathway. 30,31 The db/db mice were orally administered HED for up to 6 weeks. This natural extract inhibited the translocation of Smad2/3 and Smad4 to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK includes four subfamilies, three of which have been well characterized: extracellular regulated kinase (ERK 1/2), c-jun N-terminal kinase (JNK), and p38-MAPK. After oxidative stress increase, MAPK downstream signaling may lead to myocardial hypertrophy and fibrosis [6, 41, 42, 44]. We therefore evaluated MAPK protein expression and observed that p-ERK and p-JNK were lower in AS-NAC than AS.…”
Section: Discussionmentioning
confidence: 99%